Caprice : a Stockman's Daughter. - Pilkington Garimara, Doris (David Unaipon Award Winners Series., 2012)
This fictional account of one woman's journey to recover her family and heritage won the 1990 David Unaipon Award for Aboriginal and Torres Strait Islander writers. Set in the towns, pastoral stations and repressive institutions of Western Australia, it is a moving story of three generations of Yamatji women. Kate begins her journey with the life of her grandmother, Lucy, a domestic servant. She discovers how her mother's love for a young Aboriginal stockman ended tragically. Kate was born into the Settlement, taught Christian doctrine and trained for a career as a domestic. Gradually and pain.